2022
DOI: 10.1017/hpl.2022.18
|View full text |Cite
|
Sign up to set email alerts
|

How the laser beam size conditions the temporal contrast in pulse stretchers of chirped-pulse amplification lasers

Abstract: In this work, we propose and verify experimentally a model that describes the concomitant influence of the beam size and optical roughness on the temporal contrast of optical pulses passing through a pulse stretcher in CPA laser systems. We develop an analytical model that is capable of predicting the rising edge caused by the reflection from an optical element in a pulse stretcher, based on the power spectral density of the surface and the spatial beam profile on the surface. In an experimental campaign, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This demonstrated that the proposed solution has the advantage of a high signal-to-noise ratio. In addition, the diverse physical requirements of high-energy laser physics experiments require our solution to achieve various waveform outputs such as short pulses [28], short pulse trains, and square waves. We simulated the shaped output signal under the pump using a single short pulse, a short pulse sequence, and the waveforms used in ICF experiments [29], as shown in Figure 5.…”
Section: Simulations Resultsmentioning
confidence: 99%
“…This demonstrated that the proposed solution has the advantage of a high signal-to-noise ratio. In addition, the diverse physical requirements of high-energy laser physics experiments require our solution to achieve various waveform outputs such as short pulses [28], short pulse trains, and square waves. We simulated the shaped output signal under the pump using a single short pulse, a short pulse sequence, and the waveforms used in ICF experiments [29], as shown in Figure 5.…”
Section: Simulations Resultsmentioning
confidence: 99%
“…The remaining rising slope leading to the main pulse is clearly resolved and not masked by the limitations of the measurement tools. Its origin has recently been shown to lie in the combination of beam size and surface imperfection of the stretcher setup necessary for the CPA scheme and its mitigation and control is still being further investigated [32][33][34] .…”
Section: Temporal-contrast Improvement and Controlmentioning
confidence: 99%
“…Here, the contrast enhancement magnitude is in the range of two to three per mirror but comes at the cost of mirror replacement on a regular basis and an energy loss of 20%-30% per mirror. Unlike the previous methods, PMs address all sources of contrast degradation at once and they offer a very robust and reliable way to improve the temporal contrast, including the ps-pedestal, which is inherently coupled to the use of a stretcher and compressor in CPA systems [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%